The Utilization of AI (Artificial Intelligence) in Arabic Language Learning: A Study of the Reasons And Experiences of Arabic Language Education Students (PBA) at the College of Qur’an Sciences (STIQ) Amuntai - Rahmah, Nurul Awalia; Ramadhani, Dony Ahmad; Nuruddaroini, M. Ahim Sulthan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the reasons and experiences of students in the Arabic Language Education Study Program (PBA) in utilizing AI (Artificial Intelligence) as a medium for learning Arabic, identifying the forms of AI utilization used, and examining its role in supporting the development of Arabic language skills. The research uses a descriptive-qualitative approach with semi-structured interviews with students who actively use AI, as well as through literature studies to analyze the reasons and experiences of students in using various AI platforms. The results show that students utilize AI based on reasons of time efficiency and the need for independent understanding of learning materials, especially in helping them understand vocabulary, improve grammar, provide harakat, and compose sentences and paragraphs. However, some challenges were still identified, such as translation inaccuracies and the risk of dependency. Overall, students viewed AI as an effective supplementary tool in Arabic language learning, provided it is verified and used wisely.